Dynamics of Hydrology on the Physico-Chemical Water Quality Parameters and Trophic State of Lake Baringo, Kenya - Nyakeya, K.; Kipkorir, K.G; Nyamora, J.M.; Odoli, C.O; Kerich, E (Africa Environmental Review Journal, 2022)
Lake Baringo is a freshwater lake situated in the Kenyan Great Rift Valley, characterized by a polymictic regime with southern inlets but without any visible outlet. How the inflowing rivers and the rise in lake water levels affect water quality is still unclear. In this study, samples were collected from May 2014 to June 2015 at sites S2, C1, C2, C3 and N2: S denoted southern part, C central region and N northern part; and analysed for a wide range of physical and chemical parameters and the trophic state of the lake also determined. During 2017, samples were collected from nine stations at sites designated inlet (S1, S2 and S3), Lake Centre (C1, C2 and C3) and offshore (N1, N2 and N3). Spatial differences were determined by Analysis of Variance (ANOVA). All the physicochemical parameters (i.e. for 2017) demonstrated significant (P <0.05) spatial variations. Equally, spatial-temporal differences were noted for one year study period of June 2014 to May 2015 (P <0.05). Data collected for one year indicated a somewhat different trend from what was witnessed on data of 2017. Stations that demonstrated high values of the measured parameters during the 2017 sampling (i.e. temperature for S2, 26.8oC) recorded reduced levels in the one year sampling (26.0oC). However, results from the 2017 study period showed variation from one station to another (p<0.05). The ecological status of the lake as measured by the water quality studies carried out in the present study has changed in comparison with the previous studies because the general trend is indicative of an improved system due to rise in water levels. The study recommends regular monitoring in order to discern the erratic changes witnessed with the changes in water levels leading to deviation of the physico-chemical water quality parameters from the past studies.